Targeting translation: eIF4E as an emerging anticancer drug target. (18th January 2016) - Lu, Chunwan; Makala, Levi; Wu, Daqing; Cai, Yafei
Abstract : The translation initiation factor eIF4E mediates a rate-limiting process that drives selective translation of many oncongenic proteins such as cyclin D1, survivin and VEGF, thereby contributing to tumour growth, metastasis and therapy resistance. As an essential regulatory hub in cancer signalling network, many oncogenic signalling pathways appear to converge on eIF4E. Therefore, targeting eIF4E-mediated cap-dependent translation is considered a promising anticancer strategy. This paper reviews the strategies that can be used to target eIF4E, highlighting agents that target eIF4E activity at each distinct level.